Islamic resource management principles and the National Forestry Policy - Nuruddin, Ahmad Ainuddin; Hamzah, Mohd Basri; Md Derus, Abdul Rahman; Harun, Jalaluddin (1989)
The rapid depletion of forest resources is rapidly becoming a global concern. Is there any other alternative principles of management that can guide scientists and policy makers than the present bias towards the consumerist approach? This paper will discuss concepts of resource management from the Islamic perspectives. Islamic principles relating to the role of man, the purpose of creation, characteristics and utilization vis-a-vis natural resources will be elaborated. The National Forestry Policy will be assessed from this Islamic view point.